Regeln in DaF-Übungsgrammatiken: sprachwissenschaftliche und sprachdidaktische Perspektiven - Di Meola, Claudio (Linguistik Online, 2025)
The present article investigates German grammars for foreign learners in a linguistic and didactic perspective. In the introductory part, criteria for scientific and didactic adequacy are elaborated. The main part consists in the analysis of five recent and widespread grammars for different language levels, pertaining to three case studies: nominal gender, prepositions with dative/accusative government, future tenses. It is shown that these grammars display only a partial scientific adequacy in so far important rules are not mentioned. From a didactic point of view the most important shortcoming is a lack of systematicity as single rules are being listed without showing their interconnections. Moreover, a number of rules are difficult to put in practice because they require prior grammatical knowledge. At last, there is no sensible progression between grammars for beginners and grammars for advanced learners.